The article is devoted to the impact of human resources, namely their potential in the introduction of digitalization of business processes at enterprises. It is emphasized that without the increase of human potential, the formation of creative thinking, - Зелінська, Галина Олексіївна (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2025)
The article is devoted to the impact of human resources, namely their potential in the introduction of digitalization of business processes at enterprises. It is emphasized that without the increase of human potential, the formation of creative thinking, changes in the worldview of man, the desired results related to the digitalization of business processes of the enterprise in the conditions of sustainable development are not possible. It is substantiated that the introduction of digitalization of business processes requires changes in approaches to the educational system and the system of development of human resources at the enterprise. It is determined that the development of human creative thinking is a priority in shaping human potential in the modern world. It has been found that the modernization of production and implementation of digitalization of business processes require not only prepared workers who are easily adapted to new working conditions and are ready to change their profession, be responsible for making decisions, but also capable of learning a new one. They should be objectively ready to cope with new professional functions that can perceive changes as a normal process of modern production. It is determined that digital competence is the basis for the successful functioning of the enterprise and managing its business processes in the conditions of sustainable development. It includes the skillful, critical and responsible use of digital technologies for learning, work and participation in public life. It is emphasized that developed countries of the world pay attention to the development of human potential, in the conditions of information society. Digitalization is now a demanded factor in the labor market. It was found that there are subjective obstacles to the activation of the implementation of the digital economy in Ukraine. The main ones are fragmentation, lack of systematicity, consistency, completeness, and coherence between the adoption of regulatory legal acts and the further development of mechanisms for their implementation. It is substantiated that digital technologies contribute to more efficient and responsible resource management, improve economic stability and increase the social responsibility of business, make significant changes in the system of social and labor relations, provide economic benefits, increase efficiency of activity, etc. In the course of writing the article used: Internet sources-to reveal the essence of managing human potential in the face of increasing the role of informatization of business processes; comparison - for the analysis of world trends on the development of human resources; scenario approach - to reveal a person's priority in decision making; abstract-logical-for formulation of conclusions from the study.